2017
DOI: 10.1016/j.ijoa.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of post-cesarean delivery hypoxia after spinal anesthesia with intrathecal morphine 150 μg

Abstract: Introduction Delayed respiratory depression is a feared complication of intrathecal morphine in patients undergoing cesarean delivery. The incidence, timing and risk factors for hypoxia in this population are not known. Methods Patients undergoing cesarean delivery under spinal anesthesia at a tertiary care center from October 2012 to March 2016 were included in the study. The Berlin sleep apnea Questionnaire was completed before surgery. Oxygen saturation was recorded every second for 24 hours after the ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“… 16 , 99 A prospective study in patients having a cesarean delivery with intrathecal morphine administration demonstrated that OSA and obesity were associated with approximately a 2-fold increase in risk for desaturation. 100 However, another observational analysis of 990 patients undergoing orthopedic surgery with intrathecal morphine could not find an association between OSA and adverse pulmonary events. 101 …”
Section: Intraoperative Medication Use In Patients With Osamentioning
confidence: 97%
“… 16 , 99 A prospective study in patients having a cesarean delivery with intrathecal morphine administration demonstrated that OSA and obesity were associated with approximately a 2-fold increase in risk for desaturation. 100 However, another observational analysis of 990 patients undergoing orthopedic surgery with intrathecal morphine could not find an association between OSA and adverse pulmonary events. 101 …”
Section: Intraoperative Medication Use In Patients With Osamentioning
confidence: 97%
“…Kopka et al suggest that TcCO 2 may be more effective in detecting respiratory depression compared to SpO 2 when patients receive supplementary oxygen 30 . Ladha et al studied oximetry after CS having 150 µg morphine intrathecal 31 . They found frequent mild desaturation events and increased risk in patients with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion criteria were as follows: patients with psychiatric or neuromuscular diseases; those who did not provide written informed consent; those who received anesthesia other than single-shot spinal anesthesia (multiple administrations of spinal anesthesia, epidural anesthesia, combined spinal-epidural anesthesia, and general anesthesia), those who underwent cesarean delivery following epidural labor. Women who required additional sedatives and analgesics intraoperatively, those who received oxygen administration postoperatively, those with missing data regarding demographics and respiratory monitoring, and those with respiratory monitoring within 6 hours postoperatively were excluded from data analysis [10].…”
Section: Design and Settingmentioning
confidence: 99%
“…Previous studies which monitored postpartum respiratory depression using scheduled intermittent monitoring strategy revealed low respiratory depression rates of 0%-0.26%; however, such monitoring strategy would not su ciently detect respiratory depression and its related factors have been poorly examined [7][8][9]. Although some studies that used continuous monitoring, such as capnography and pulse oximeter, revealed that the incidence of apnea and hypoxemia were much higher than those reported previously using scheduled intermittent monitoring [7,10,11], little evidence is available regarding bradypnea measured using continuous monitoring following intrathecal morphine in women who underwent cesarean delivery.…”
Section: Introductionmentioning
confidence: 99%